Improvement of Teacher Creativity Guidance and counseling in Compilation Guidance and Counseling Service Implementation Plan At SMP in Agam Regency - Neviyarni Neviyarni; Riska Ahmad; Yeni Elviza; Geandra Ferdiansa (Universitas Negeri Padang, 2020)
The preparation of the RPL BK carried out by the counseling guidance teacher has not been programmatically formulated based on a description of the needs identified based on the assumptions about the developmental tasks that should be achieved by students and the needs assessments that have been carried out in the previous stage. The inability to compile RPL-BK creatively makes students bored in following services which makes the purpose of the service not achieved. The cause of the inability of counseling teachers to produce creative RPLs is due to a lack of knowledge and a lack of time. The solution that can be given from this problem is to train the creativity of each BK teacher to be able to make the RPLBK plan attractive, so that students do not get bored following the implementation of guidance and counseling. This community service aims to provide training for BK teachers to increase creativity in making RPL so that they are able to generate new views and produce something that has never been done before and will have a good impact on the implementation of BK in schools. This research uses descriptive method through action research. The target audience in community service activities are BK teachers / counselors who work in religious districts. The techniques used in providing this training are via online via zoom meetings. The results obtained were the creativity of the guidance and counseling teachers in making RPL before carrying out guidance and counseling service activities.